Life Cycle Assessment (LCA) technique as a holistic tool for environmental impact and economic analysis of a co-pulping process - Majozi, Thokozani (University of Pretoria, 2013)
Dissertation (MEng (Chemical Engineering))--University of Pretoria, 2008.